SOCIO-PEDAGOGICAL FOUNDATIONS OF DEVELOPING SOCIAL COMPETENCE BASED ON A GENDER APPROACH (Scientific journal of the Fergana State University, 2026)
This article offers a comprehensive analysis of the concept of social competence, its nature, and its significance in personal development from a scientific perspective. It also explores the processes of developing social competence within a gender-based approach and analyzes their influence on social interaction, communication culture, and principles of gender equality in society. The article presents advanced theoretical frameworks and practical recommendations related to the topic.